A Man in His Forties with Recurrent Cat-Scratch Disease - Sara López-Rueda; Benjamin Valente-Acosta; Adrian Murillo-Zolezzi; Francisco Moreno-Sánchez; Irma Hoyo-Ulloa; Jesús Javier Baquera-Heredia (Case Reports in Infectious Diseases)
Cat-scratch disease (CSD) is a self-limited zoonotic infection transmitted by felines caused by the Gram-negative bacillus Bartonella henselae. It usually presents with lymphadenopathy and constitutional symptoms that resolve within eight weeks, with, or without antibiotic treatment. The diagnosis is made by serology, molecular diagnosis in a biopsy, or a positive culture. The recurrence or reactivation of B. henselae has rarely been reported. We present the case of a 45-year-old man with a history of CSD two years before who presented to the clinic with groin lymphadenopathy. The patient had a history of close contact with felines though no known risk exposure was reported. The diagnosis was made with a positive serology suggestive of recent infection along with histopathological changes suggestive of CSD. Subsequently, azithromycin was administered with complete resolution of symptoms.